Pensar o governo : o éthos ﬁlosóﬁco como prática de liberdade na crítica do presente em Foucault - Helrison Silva Costa (2021)
When we analyze the problems placed by the issue of government in the genealogy of Michel Foucault since 1978, it is possible to perceive a close relationship between critical attitude and parrhesia in the author's last studies. Considering that parrhesia and critical attitude are constituted as philosophical éthos in the history of governmentality, at the point where is intersect and articulate government of self and others, what link there may be between these two éthos and how it is established? We assume that this bond arises in the production of freedom practices and, therefore, is in line with the foucauldian philosophical project of a critique of truth and power that take places as "ontology of the present". Thus, we may ask: how can foucauldian criticism be performed as a historical-philosophical practice activated by the critical éthos and the parrhesiastic éthos? Our work therefore consist in examining the critical attitude and parrhesia trying to understand how the critical éthos and the parrhesiastic éthos help the autor to think philosophical activity as a practice that interrogates the current moment in which we live. Thus, we can better understand the conception of philosophy and politics that appears in the author, linked to the “problematization” of government and freedom practices.